Variation of caesarean section rates in Sub-Saharan Africa: A literature review - Dikete M; Coppieters Y; Trigaux P; Fils JF; Englert Y; Simon P; Zhang W (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2019)
Introduction: Ensuring access to quality caesarean section (CS) care is a key millenium development strategy and the next sustainable development goal to reduce maternal and infant mortality. The WHO recommends that the caesarean section rate should not exceed 10-15%. The objective of our analysis is to document the variability of caesarean section rates in Sub- Saharan Africa. Material and method: we carried out a review of 26 studies for the simple proportions of events using the R metafor package (Viechtbauer, 2010). The studies were selected in the following way: the type of study, target population and keys words (such as intra operative complications, caesarean sectionutilization, maternal mortality or perinatal mortality or morbidity and caesarean section, Africa south ofthe Sahara or sub Saharan Africa). We performed a random-effects meta-analysis, and heterogeneity was assessed using the I2 value.